2003
DOI: 10.1016/s0009-9236(03)90425-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel interactions in the oral absorption of hydrophilic cations (HCS): A clinical study with ranitidine and famotidine

Abstract: Clinical Pharmacology & Therapeutics (2003) 73, P19–P19; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Interestingly, the absorption of ranitidine from the terminal ileum of rat small intestine is quite extensive and higher than that observed from duodenum and midgut (40). Additionally, deconvolution analysis of the absorption data for coadministered ranitidine and famotidine in humans demonstrated that a significant decrease in the oral absorption of famotidine occurred exclusively in the later stages of absorption when administered in the presence of ranitidine (41). These results suggest that modulation of intestinal transport by pH and/or differences in transporter expression levels may play an important role in the site-dependent absorption of ranitidine and similar hydrophilic cations.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, the absorption of ranitidine from the terminal ileum of rat small intestine is quite extensive and higher than that observed from duodenum and midgut (40). Additionally, deconvolution analysis of the absorption data for coadministered ranitidine and famotidine in humans demonstrated that a significant decrease in the oral absorption of famotidine occurred exclusively in the later stages of absorption when administered in the presence of ranitidine (41). These results suggest that modulation of intestinal transport by pH and/or differences in transporter expression levels may play an important role in the site-dependent absorption of ranitidine and similar hydrophilic cations.…”
Section: Discussionmentioning
confidence: 90%
“…Such a mechanism may explain the observed high bioavailability of this hydrophilic compound in humans. Interestingly, a clinical study designed to investigate if oral absorption of ranitidine is saturable clearly established the presence of a saturable component in the intestinal absorption of this drug (20). Whether the saturable paracellular transport mechanism exists in human intestine remains to be determined because direct evidence to link the in vitro studies and modeling of ranitidine transport in the Caco-2 system with its intestinal absorption in humans is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…2 A recent clinical study confirmed that ranitidine and famotidine are absorbed across the intestinal epithelium, at least in part, via a saturable transport mechanism as evidenced by the observation that orally administered ranitidine (300 mg) attenuated the oral bioavailability (absorption) of coadministered famotidine (40 mg). 4 Caco-2 studies also revealed that ranitidine and famotidine caused a saturable, concentration-dependent increase in the transepithelial electrical resistance (TEER) across the cell monolayers. This phenomenon was attributed to blocking of anionic sites in the paracellular space that facilitate transport of Na + ions (and other cations) across Caco-2 cell monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophilic cationic drugs such as ranitidine and famotidine (Figure ) cross the intestinal epithelium via a predominantly paracellular route of transport as determined by studies in the Caco-2 cell culture model of intestinal epithelia. Recent work in our laboratory has revealed both saturable and nonsaturable components to the absorptive transport of such compounds across Caco-2 cell monolayers . A recent clinical study confirmed that ranitidine and famotidine are absorbed across the intestinal epithelium, at least in part, via a saturable transport mechanism as evidenced by the observation that orally administered ranitidine (300 mg) attenuated the oral bioavailability (absorption) of coadministered famotidine (40 mg) . Caco-2 studies also revealed that ranitidine and famotidine caused a saturable, concentration-dependent increase in the transepithelial electrical resistance (TEER) across the cell monolayers.…”
Section: Introductionmentioning
confidence: 99%